Pengukuran Kinerja Keuangan Berbasis Value For Money : Studi Empiris Pada Badan Pengelolaan Keuangan Dan Aset Daerah (BPKAD) Kabupaten Lamongan Tahun 2019 - 2023 - Nihayatuz Zuhuriyyah, Nabilatun; Nufaisa, Nufaisa (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to measure the financial performance of the Regional Financial and Asset Management Agency (BPKAD) of Lamongan Regency in 2019–2023 based on the Value for Money concept which includes the principles of economy, efficiency, and effectiveness. The method used is descriptive qualitative with a case study approach, collecting primary data through interviews and observations and secondary data from the Budget Realization Report (LRA) and other supporting documents. The results of the ratio analysis show that the management of regional spending during this period is classified as economical with an average ratio of 93.61%, and balanced efficient with an average efficiency ratio of 100.70%. However, the effectiveness of regional revenue is still fluctuating and mostly ineffective, mainly due to the low realization of revenue from taxes, levies, and grants. The implications of this study emphasize the need to increase the utilization of regional potential and revenue management so that financial targets can be achieved optimally, so that public services and regional development can run more effectively and sustainably.